Community Behavior in Prevention of Dengue Hemorrhagic Fever through Activities of Eradication of Dengue Fever Mosquito Nests - Tuhu Pinardi; Aries Prasetyo (Humanistic Network for Science and Technology (HNST), 2017)
Dengue Hemorrhagic Fever is one of the main public health problems in Indonesia. The number of sufferers and the area of spread are increasing along with increasing mobility and population density. Community Service Results in 2016 found that the larvae-free number from the three hamlets in Banjarejo village was still low and the potential for cases of dengue hemorrhagic fever. This was a descriptive study with a cross sectional approach. The population of this study was 1037 the head of the family. The sample size was 88 families, selected by proportional random sampling. The research instrument were questionnaires and observation sheets. Data were analyzed using descriptive statistics, in the form of frequency and percentage. Data from research on respondents' perceptions of support from community leaders were 48 respondents (53.3%). There were 5 respondents (57.8%) actions in Eradication of Dengue Fever Mosquito Nests were sufficient and 11 respondents (12.2%) actions in Eradication of Dengue Fever Mosquito Nests were good. The role of community leaders has a positive effect on the Eradication of Dengue Fever Mosquito Nests. Keywords: Dengue hemorrhagic fever, Community leader, Eradication of mosquito nests